PENGEMBANGAN USAHA BUDIDAYA IKAN SISTEM BIOFLOK DI KOTA PALU PROVINSI SULAWESI TENGAH - Mustapa, Saprudin; Noer, Hasmari; Yahya, Fachrudin A. (Jurnal Perikanan Unram, 2025)
The fisheries sector plays a crucial role in food security and the economy, particularly through aquaculture. One rapidly growing method is the biofloc system, which enhances production efficiency by utilizing microorganisms to process organic waste into biomass that can be consumed by fish. This technology not only improves feed efficiency but also reduces environmental impact. Palu City holds great potential for developing biofloc-based aquaculture due to its abundant water resources and supporting infrastructure. This study aims to identify the factors influencing biofloc aquaculture businesses in Palu City, analyze their technical and economic feasibility, and formulate sustainable development strategies. The research employs a descriptive qualitative and quantitative approach using purposive sampling techniques. The applied analysis includes descriptive analysis, business feasibility analysis (BCR, BEP, and PP), marketing margins, and SWOT analysis. The findings of this study are expected to provide strategic recommendations for fish farmers and stakeholders to develop biofloc systems more effectively and sustainably in Palu City.